The White and Red Terror in the Eastern Part of Viru County in 1917–1919 - Jürman, Ants (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2021)
From 1917 to 1919, terror against political enemies was used by the Bolsheviks, the German occupation authorities, the Commune of the Working People of Estonia that acted as a puppet government for Soviet Russia, and also by the young Republic of Estonia, as they tried to protect their rule. Compared to the rest of Estonia, the eastern parts of Viru County, especially Narva and Jaanilinn, are notable for a relatively higher number of victims. Estonians constituted the majority of the victims of the terror from both sides, but less is known about the fact that many Finnish members of the Red Guards were among those who fell when the Estonian Army and the Finnish volunteers liberated the city of Narva in January 1919.